Atanassov's intuitionistic fuzzy Γ - hyperideals of Γ - semihypergroups - Ersoy, Bayram Ali; Davvaz, B. (IOS PRESS, 2013)
The notion of intuitionistic fuzzy sets was introduced by Atanassov as a generalization of the notion of fuzzy sets. In this paper, we apply this concept to Gamma - semihypergroups and we introduce the notion of an intuitionistic fuzzy Gamma - hyperideal of a Gamma - semihypergroup. Then, we investigate some properties connected with intuitionistic fuzzy Gamma - hyperideals in a Gamma - semihypergroup.
Keywords: Hyperstructure; semihypergroup; Gamma - semihypergroup; intuitionistic fuzzy set; Gamma - hyperideal; intuitionistic fuzzy Gamma - hyperideal; HYPERGROUPS; IDEALS; Computer Science